Francisco Vivar, La Numancia de Cervantes y la memoria de un mito. Biblioteca Nueva, Madrid, 2004; 174 pp. - Hernández Trujillo, Carlos Oswaldo (El Colegio de México, 2008)
Se reseñó el libro: La Numancia de Cervantes y la memoria de un mito.